2005
DOI: 10.1111/j.1471-4159.2005.03067.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport characteristics of N‐acetyl‐l‐aspartate in rat astrocytes: involvement of sodium‐coupled high‐affinity carboxylate transporter NaC3/NaDC3‐mediated transport system

Abstract: We investigated in the present study the transport characteristics of N-acetyl-L-aspartate in primary cultures of astrocytes from rat cerebral cortex and the involvement of NA + -coupled high-affinity carboxylate transporter NaC3 (formerly known as NaDC3) responsible for N-acetyl-L-aspartate transport. N-acetyl-L-aspartate transport was NA + -dependent and saturable with a Michaelis-Menten constant (K m ) of 110 lM. NA + -activation kinetics revealed that the NA + to-N-acetyl-L-aspartate stoichiometry was 3 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
2
35
1
5
Order By: Relevance
“…A reabsorption of these compounds by hNaDC1 located in the apical [14] is unlikely, because NaDC1 has a low affinity for C5 dicarboxylates ( [23] and own unpublished results). NaDC3 is not only localized in the basolateral membrane of human and rat kidneys [24] but also in rat astrocytes [25,26] where it mediates αKG-inhibitable transport of [ 14 C]N-acetyl-L-aspartate, a compound with a dicarboxylic acid like structure. It needs to be established which role hNaDC3 plays in the brain of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…A reabsorption of these compounds by hNaDC1 located in the apical [14] is unlikely, because NaDC1 has a low affinity for C5 dicarboxylates ( [23] and own unpublished results). NaDC3 is not only localized in the basolateral membrane of human and rat kidneys [24] but also in rat astrocytes [25,26] where it mediates αKG-inhibitable transport of [ 14 C]N-acetyl-L-aspartate, a compound with a dicarboxylic acid like structure. It needs to be established which role hNaDC3 plays in the brain of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this route of NAA clearance, extracellular NAA can arise through efflux from neurons along the steep intraneuronal to extracellular concentration gradient, or through the enzymatic release of NAA from NAAG by the action of glutamate carboxypeptidase II on the surface of astrocytes (Berger et al, 1999;Blakely et al, 1988;Cassidy and Neale, 1993b;Slusher et al, 1992). Extracellular NAA has been shown to be preferentially taken up by astrocytes as opposed to neurons (Sager et al, 1999b) via the dicarboxylate transporter NaDC3, (Fujita et al, 2005;Ganapathy and Fujita, 2006;George et al, 2004;Huang et al, 2000), and NAA appears in urine at low micromolar concentrations, indicating that there is continuous efflux from the brain (Kelley and Stamas, 1992;Kvittingen et al, 1986;Miyake et al, 1982). Normal serum NAA levels are very low, and this may be due to glomerular filtration in the kidneys (Hagenfeldt et al, 1987).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
“…However, other results have failed to show significant ASPA activity in O2A cells in culture (Madhavarao et al, 2002), and immunohistochemical studies have shown a complete lack of ASPA expression in astrocytes in the brain . Considering the facts that astrocytes form a significant portion of the blood-brain barrier, and that NAA is normally found in the urine (Hagenfeldt et al, 1987;Kvittingen et al, 1986), and that astrocytes express a sodium-dependent transporter for the uptake of extracellular NAA (Fujita et al, 2005), it seems likely that these glial cells take up extracellular NAA and excrete it to the circulation. In this regard it is interesting to note that we have observed NAAimmunoreactivity in a sub-population of brain endothelia ( Figure 5).…”
Section: Naa Transporters and Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to test our hypothesis that the NAAGS gene encodes NAAG synthetase, we initially expressed NAAGS (variant v1) in primary astrocytes, which are known to express the NAA transporter NaDC3 (39). Transfected cells were incubated for 4 h with [ 14 C]glutamate (in the absence or presence of unlabeled 10 mM NAA in the culture medium).…”
Section: Naag Synthesis In Naags-expressing Cells-no In Vitromentioning
confidence: 99%